Clinical effect of enoxaparin on international normalized ratio following hepato‐pancreatico‐biliary and gastroesophageal resection. Issue 1 (7th June 2018) - Kelecy, Matthew W.; Shutt, Travis; Rostas, Jack; Martin, Robert C. G.
Abstract : Background and Objectives: Enoxaparin inactivates factor Xa via a complex formed after binding to circulating anti‐thrombin III. This mechanism is reported not to alter hemostatic measures such as clotting time, PT, or PTT. To date, no clinical trials have shown a causal relationship between the clinical/pharmacological effects of enoxaparin on international normalized ratio (INR). The aim of our study is to show the clinical effect of enoxaparin on INR. Methods: Patients ( N = 350) were reviewed from our prospective IRB approved databases undergoing gastroesophageal or hepatobiliary surgeries. INR levels were recorded for 6 days: pre‐operative to 5 days after surgery. Results: Patients ( N = 289) received enoxaparin daily starting post‐operative day 1, while 61 patients who did not receive enoxaparin were used as controls. The mean post‐operative INR in both the 30 and 40 mg groups were both significantly higher than the mean post‐operative INR of the control group ( P = 0.015 and P = 0.00075, respectively); however postoperative hemoglobin levels were not significantly lower in the enoxaparin versus control. Conclusion: This is the first clinical evidence of the effect of enoxaparin on INR in patients undergoing abdominal surgeries for malignancies. We demonstrate an increase in the INR for patients who received enoxaparin for post‐operative VTE prophylaxis.